1991
DOI: 10.1093/jnci/83.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Studies With RP 56976 (Taxotere): A Semisynthetic Analogue of Taxol

Abstract: RP 56976 (taxotere), a new semisynthetic analogue of taxol, is a potentially important chemotherapeutic agent for the treatment of cancer. We report here that this drug is a potent inhibitor of cell replication and, like taxol, promotes the in vitro assembly of stable microtubules in the absence of guanosine triphosphate and induces microtubule-bundle formation in cells. Compared with taxol, RP 56976 is slightly more active as a promoter of tubulin polymerization. As an inhibitor of cell replication, RP 56976 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
268
1
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 609 publications
(279 citation statements)
references
References 0 publications
8
268
1
2
Order By: Relevance
“…This induces a disruption of the equilibrium within the microtubule system and ultimately leads to cell death Ringel et al, 1991;. Docetaxel has been studied in many murine tumour models, showing activity against subcutaneous (s.c.) B16 melanoma, MX-l mammary cancer, C38 colon carcinoma, CX-1 colon carcinoma, LX-1 lung carcinoma, s.c. early stage pancreatic ductal adenocarcinoma (P03), S.C. colon adenocarcinoma 51 (C51), SK MEL-2 melanoma and OVCAR-3, HOC 8, HOC 10 and HOC 22 ovarian carcinomas (Denis et al, 1988;Bissery et al, 1991;Harrison et al, 1992, Nicoletti et al, 1992.…”
mentioning
confidence: 99%
“…This induces a disruption of the equilibrium within the microtubule system and ultimately leads to cell death Ringel et al, 1991;. Docetaxel has been studied in many murine tumour models, showing activity against subcutaneous (s.c.) B16 melanoma, MX-l mammary cancer, C38 colon carcinoma, CX-1 colon carcinoma, LX-1 lung carcinoma, s.c. early stage pancreatic ductal adenocarcinoma (P03), S.C. colon adenocarcinoma 51 (C51), SK MEL-2 melanoma and OVCAR-3, HOC 8, HOC 10 and HOC 22 ovarian carcinomas (Denis et al, 1988;Bissery et al, 1991;Harrison et al, 1992, Nicoletti et al, 1992.…”
mentioning
confidence: 99%
“…The anti-tumor mechanism of docetaxel is completely different from that of 5FU and CDDP (6). Docetaxel promotes the polymerization of tubulin and inhibits the disassembly of microtubules, thereby blocking cell division at the M phase during the cell cycle.…”
Section: Introductionmentioning
confidence: 98%
“…This disruption of the normal equilibrium of tubulin function ultimately leads to cell death primarily during the G2/M-phase of the cell cycle [34]. As an inhibitor of microtubule depolymerization, docetaxel is approximately twice as potent as paclitaxel, prompting many investigators to study its cytotoxicity in a variety of cell lines [25]. Further clinical studies have shown docetaxel to have potent anti-tumor activity against several human tumors, including ovarian [20], anthracycline-resistant breast [4,30], non-small cell lung [6,10,12] and head and neck squamous cell cancer [7,31].…”
Section: Discussionmentioning
confidence: 99%